Diversidade da nematofauna em pomares de videira com sintomas de declínio e agressividade de Mesocriconema xenoplax - Kuhn, Paulo Roberto (2015)
Had it aimed in this study to survey the plant-parasitic nematodes in the Serra Gaúcha vineyards with symptoms of decline; evaluate the pathogenicity and aggressiveness Mesocriconema xenoplax in vine and peach; and test the susceptibility of weed and forage the two population M. xenoplax.First we evaluated the diversity of genres and populcional density of plant-parasitic nematode genera associated to nine vineyards of the Serra Gaúcha.In the survey the Mesocriconema genera were identified; Ogma; Meloidogyne; Paratrichodorus; Helicotylenchus; Xiphinema; Pratylenchus; Hemicicliophora and free-living nematodes, and the free living nematodes and Mesocrinema apresentram in more densely populated than others.The following was characterized biochemically by electrophoresis populations and morphological and morphometric Meloidogine three populations of ringed nematode Mesocriconema genre with the highest population levels, eight esterásticas bands were identified and four phenotypes of esterase (Est) which corresponded to the species M. javanica Est J3, M. incognita Est I2, M. arenaria and M. hapla A2 Est Est H1. the only species identified the Mesocriconema gender was Mesocriconema xenoplax.Subsequently, three cultivars room (Concord, Niagara pink, Claret) and a rootstock (Paulsen) vine and the cultivar Peach Capdbosq were inoculated or not with 2000 M. xenoplax specimens from four different populations, coming from three vineyards Serra Gaúcha and a coming of peach orchard in the city of Pelotas, Brazil, kept in the collection by Embrapa Clima Temperado.Every 30 days was determined chlorophyll content of plants. After 180 inoculation, the plants of each treatment were measured morphologically and analyzed for length of the main branch, fresh weight of aerial part, stem diameter, main root length, fresh weight of root and leaf area. Also enzymatic activity was determined peroxidase branches of each plant.Then the soil in each sample was processed for determination of the final population and calculating the reproduction factor of each population of M. xenoplax each cultivar to evaluate the pathogenicity of the nematode and aggressiveness.Among the populations of M. xenoplax tested, it was observed that there is a difference as to the aggressiveness characterizing the population 2 of from vine to be the most aggressive, which is pathogenic to all genotypes of grapevine, the board was cultivating the most susceptible.In the evaluation of forage species to populations d M. xenoplax tested, vetch, sunn hemp, bermudagrass and grass evergreen, provided higher FR M. xenoplax, being considered as susceptible host plants and vine groves and peach with a history of presence of M. xenoplax must be eliminated. Unlike grasses oat; oats; ryegrass; millet and sorghum can be used as cover crops in orchards and vine peach contaminated with Mesocriconema xenoplax due to its low reproducibility in these plants.